The Medicinal Plants of Hatikote Forests of District Mayurbhanj, Orissa - Need for Conservation - Kumar, J.; Rout, S. D.; Das, M. K. (Indian Forester, 2006)
The Hatikote forest area in Baripada Forest Division, Mayurbhanj District (Orissa) is endowed with a rich wealth of medicinal plants. The invaluable resource of medicinal plants is however, under serious threat from severe depletion due to grazing, fire, pilferage and social indiscretions in utilization. In the present paper 65 medicinal plants belonging to 34 families of flowering plants are tabulated with information about local name, habitat, family, parts used and their medicinal uses. Some important endangered medicinal plants have been identified and has taken attempt for their conservation in Hatikote area for maintaining the gene pool through ex-situ conservation. Other important issues closely related to the development of in-situ conservation has been established in 200 ha. Importance has been given towards public by which they can conserve their natural forest through identification, establishment a germ plasm banks of the selected species, procurement of seeds of different plots and water conservation by gully plugging. In pursuance of this goal, some management techniques has been developed for the protection and smooth management of the area through protection against grazing and illegal entry of people, tending operation, soil and water conservation, plantation, fire protection, entry point activities and final harvesting of medicinal plants.